(3eLGR GdbQBfs - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe GdTGaYj GdSdej GdOeTbj GdeUQj, SdWGf GdYdeGA YR GdOjf Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3GdaUd GdKGef hGdGQHYhf ai CeKdI MPa GdeVGaGJ Ydi JQJjH GdShQ hGdBjGJ s
(3BNQgG (B:s
(3jfJgi Hbhdg GdKGdK YTQ fcM CNJ ef jJRhL dCf aYdi CNa ef jaYd adPdc cKQ PcQ GdfcGM s
(3GdMHQ dhfg Hfi HGgJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1590s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdHdGZIs